Key performance and training parameters in primary total hip arthroplasty – an expert consensus using the Delphi technique. Issue 3 (May 2023) - Howgate, Daniel; Garfjeld Roberts, Patrick; Kendrick, Ben; Rees, Jonathan
Aims: Primary total hip arthroplasty (THA) is a commonly performed and successful operation which orthopaedic trainees must demonstrate competence in prior to completion of surgical training. An assessment of agreement between surgical trainers regarding the critical steps of a primary THA has never been undertaken. The aim of this study was to define and rank the key steps of a primary THA regards ease of teaching and their importance in achieving the best patient outcome. Materials and methods: The Delphi technique with 3 iterative rounds was used to establish expert group consensus. The benchmark for consensus was set at an 80% agreement in any category for each step of a THR. The intra-class correlation coefficient (ICC) was used to report on the inter- and intra-rater reliabilities between and within participants responses respectively in rounds 2 and 3. Results: 50 consultant orthopaedic hip surgeons completed round 2, and 28 completed round 3. Overall, 27 steps (54 parameters) were identified, with 16 parameters achieving consensus agreement for their impact on patient outcome, and 17 for ease of teaching. The inter-rater ICC for patient outcome parameters was 0.89 and 0.92 in rounds 2 and 3 respectively while for teaching parameters it was 0.82 and 0.73. 50% of surgeons agreed that acetabular reaming, assessing and accurately restoring leg length, and acetabular cup anteversion were the 3 most difficult steps to teach trainees, while 90% agreed these 3 steps were substantially important to patient outcome. Another 5 steps achieved consensus for their substantial impact on patient outcome but failed to achieve consensus for ease of teaching. Conclusions: The results of this expert consensus have produced a rank-order list of the key steps in primary THA, which may be used for orthopaedic curriculum development and guiding focused improvements for surgical training in primary THR including simulation.